Hasrat Mohani’s Letter Writing in British Prison - Dr. Aneela Saleem; Dr. Ali Bayat (Zaban-o-Adab, 2022)
Mevlana Hasrat Mohani was a great Urdu literary personality, His literary aspects are diverse. Apart from the high position he achieved in poetry, his prose writings also are important references to his identity. Mushahidaat.-E-Zindaan, Tazkiratu Shuara, Urdu.E.Mualla, Intekhaab-E-Dawaveen, Nikaat-E-Sukhan, a large number of literary essays, political speeches and literary journals are the best examples. His letters (written in prison) are a very important asset. From these letters one can come to know about Hasrat’s personality, Habits and era are known as well as his personal and political life, Prison life and conditions and the state of Swadeshi business also becomes clear. In the paper under study, efforts are made to bring into light various aspects of Hasrat’s personal and literary life.